Tożsamość Todda. Mózg między filozoficzną neurosferą a literacką (meta)fikcją - Nowak, Ewa (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The paper explores hybrid identities of main characters in chosen contemporary authors as Kafka, Dürrenmatt, Bulgakov, Dukaj, and in particular Brown. They all contribute to the posthumanist literary genre and to better comprehension of condition posthumana as a leading utopia in the age of advanced technologies. The author argues for affinities between the human and the non-human brain, far beyond the anthropocentrism and anthropodenialism controversy.